How an eco-school sanitation community of practice fosters action competence for sanitation management in a rural school : the case of Ramashobohle High School Eco-Schools Community of Practice in Mankweng circuit Polokwane Municipality Capricorn district in Limpopo Province, South Africa - Manaka, Ngoanamoshala Maria (Rhodes University, Faculty of Education, Department of Education, 2011)
Providing adequate sanitation facilities for the poor remains one of the major challenges in all developing countries. In South Africa, an estimated 11,7% of the schools are without sanitation. The South African government has a constitutional responsibility to ensure that all South Africans have access to adequate sanitation. When sanitation systems fail, or are inadequate, the impact of the health of the community, on the health of others and the negative impact on the environment can be extremely serious. In rural South African schools, many Enviro-Ioo toilets are available today. They are designed to suit a variety of water scarce areas and where there is a high risk of contamination of ground water resources. It is important to realize that any Enviro-Ioo system programme requires an education programme to ensure that the principles of use and maintenance are clearly understood by the user group. Their maintenance requires more responsibility and commitment by users. This study is an interpretive case study that indicates how sanitation in a rural Ramashobohle High School in Polokwane municipality was managed through an EcoSchools Sanitation Community of Practice, and how this developed action competence for sanitation management in the school. The study established that the earlier practice and knowledge of the Ramashobohle Eco-Schools community of practice exercised in maintaining Enviro-Ioo systems was inadequate; unhealthy and unsafe according to the data generated through focus group interviews, observations, interviews, action plan, workshops and reflection interviews. The data generated also indicates that the Eco-Schools community of practice was not committed to maintaining sanitation in their school because they were not sharing sanitation knowledge; they were not communicating and not updating one another concerning Enviro-Ioo systems maintenance as they had no adequate knowledge as to how to maintain the facilities; and the school management was also not supportive and was not taking responsibility. The study shows how this situation was turned around as an Eco-Schools Sanitation Community of Practice focussed on developing action competence in the school community. It provides a case based example of how knowledge and action competence, supported by an Eco-Schools Community of Practice, can find and implement solutions to inadequate sanitation management practices in rural schools, and shows how members of the school community can be engaged in learning how to manage and maintain school sanitation systems through a participatory process that develops action competence. The study points to important dimensions of developing action competence, such as providing knowledge and demonstrations, inviting experts to the school, involving learners in observations and monitoring and in ensuring that adequate facilities are available. In particular, a workshop conducted by Enviro-Ioo consultants, organised and supported by the Eco-Schools Sanitation COP, together with a follow up action plan, provided the main impetus for changes in practice in the school and served to support action competence development. Finally the study provides research findings and recommendations for further research.
Keywords: Sanitation -- South Africa -- Management -- Citizen participation; Public utilities -- South Africa -- Management -- Citizen participation; Sanitation, Rural -- South Africa; Sanitation -- Study and teaching -- South Africa; School children -- Health and hygiene -- South Africa; School hygiene -- South Africa; Sanitation -- Health aspects -- South Africa